(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The purpose of the research to provide an overview of technology transfer process to potential readers. The topicality of this issue in the world and the state of Latvian research works with the related topic was analyzed and presented in the paper. The author reviewed experiences of colleagues from other universities for identification main concepts used in this field and existing difficulties to perform technology transfer. The anticipated outcome of this review is the identification of information technology transfer model that could be used for transferring research results from Academia to Business Sector.